A high performance wearable strain sensor with advanced thermal management for motion monitoring - Cenxiao Tan (Nature Portfolio, 2020)
Though stretchable strain sensors are attractive for next-generation applications due to their high sensitivity, heat generated in these devices limits their reliability. Here, the authors report boron nitride nanosheet-based stretchable strain sensors with enhanced thermal management.